Anaesthetic Management for a Patient with Uterine Perforation Due to Gestational Trophoblastic Disease with Hyperthyroidism - wullur, caroline; Rismawan, Budiana (Majalah Anestesia dan Critical Care, 2015)
Gestational trophoblastic disease originates from abnormal proliferation of molar tissue and most of them are not complicated. However, life threatening condition such as hyperthyroidism may occur. Often, the diagnosis of hyperthyroid state is a retrospective one, as it can be missed in the emergency scenario of patient requiring molar evacuation. Trophoblastic hyperthyroidism poses a multiple of challenges to the anaesthesiologist. High output cardiac failure secondary to thyrotoxicosis, thyroid storm, hypertension and disseminated intravascular coagulation may occur in the perioperative period. We report a successful anaesthetic management of a patient with gestational trophoblastic disease with manifestations of hyperthyroidism whom underwent a trans-abdominal hysterectomy.